Information and communication technologies (ICT) and education in the WAEMU countries: a comparative gender analysis of higher education - Pousbila Dianda; Hamidou Ouedraogo; Hahandou Mano (Cogent Education)
This study analyzes the effect of information and communication technologies (ICTs) on higher education enrollment in seven WAEMU countries over the period 2000-2023, with a particular focus on gender disparities. To address potential endogeneity bias, the two-stage least squares method with instrumental variables (IV-2SLS) is used for the estimations. The results reveal that mobile telephony and the internet exert a positive and statistically significant effect on increased enrollment in higher education, with a more pronounced impact among men. On the other hand, fixed-line telephony, whose penetration remains low throughout the region, has no significant effect. Persistent inequalities in access to ICT limit the benefits for women and hinder their inclusion in digital higher education. These findings underscore the need for targeted policies: massively investing in mobile coverage and broadband internet, especially in rural areas; setting up subsidy or credit mechanisms to facilitate the acquisition of digital equipment by female students; integrating digital skills into higher education curricula to enhance their pedagogical use; and adopting a harmonized regional strategy among member states to strengthen the integration of digital skills in higher education. Such measures would reinforce the impact of ICT on higher education access while helping reduce gender inequalities.